Bidirectional shear behavior of stud connectors in steel‐concrete composite monorail track beams. (21st December 2022) - Li, Junhui; Liu, Zongchao; Deng, Jun; Chen, Fayang
Abstract: Stud connectors in steel‐concrete composite track beams of straddle‐type monorail transits experience longitudinal and transverse shear forces. Little is known about the effect of transverse shear forces on stud connectors; thus, further research is needed to evaluate the serviceability of steel‐concrete composite track beams. This study investigated the shear performance of stud connectors subjected to bidirectional shear force by means of modified push‐out tests and finite element (FE) analyses. The test results demonstrated that the presence of transverse shear forces significantly decreased the vertical shear strength and stiffness of the stud connectors. In addition, the group stud effect aggravated the reduction in shear strength and shear stiffness per stud under bidirectional shear forces. The transverse shear force also considerably affected the failure modes of the stud root and the damage range of the concrete. Furthermore, the numerical results were verified using the test results in terms of the load‐slip relationship and failure modes. Based on the verified FE model, the strength reduction factor of stud connectors was proposed incorporating the presence of transverse shear force, and the decreasing trend of stud shear strength under bidirectional shear force was presented. This study provides additional data for formulating design rules of stud connectors in monorail steel‐concrete composite track beams.